SUPPLEMENTARY MATERIALS FOR ENGLISH LESSON GRADE SEVEN IN ELIA CHRISTIAN MIDDLE SCHOOL - Ezra Christian Angkajaya; Josefa Mardijono (Kata Kita: Journal of Language, Literature, and Teaching, 2016)
This project is based on the writer’s internship in Elia Christian Junior High School from April, 7 to June, 5 2015 The writer thought that it was a good thing to make supplementary materials as a final project because of some problems the writer faced earlier during the internship. There was not sufficient interesting material in the textbook and lack of students’ participation in the classroom.  The writer wrote some suggested supplementary materials that he thought was good according to the analysis of the textbook to supplement the material written in the KTSP curriculum textbook. By having some creative activities during the lessons, hopefully they can change the habit of their English learning, to be more actively participated in every English class.